Identification of Acoustic Signals of Internal Electric Discharges on Glass Insulator under Variable Applied Voltage - Nasir A. Al-geelani; M. Afendi M. Piah; Ibrahim Saeh; Nordiana Azlin Othman; Fatin Liyana Muhamedin; N. F. Kasri (International Journal of Electrical and Computer Engineering (IJECE), 2016)
A Partial Discharge (PD) is an unwanted phenomenon in electrical equipment. Therefore it is of great importance to identify different types of PD and assess their severity. This paper investigates the acoustic emissions associated with Internal Discharge (ID) from different types of sources in the time-domain. An experimental setup was arranged in the high voltage laboratory, a chamber with an electrode configuration attached to it was connected to a high voltage transformer for generating various types of PD. A laboratory experiment was done by making the models of these discharges. The test equipment including antennas as a means of detection and digital processing techniques for signal analysis were used. Wavelet signal processing was used to recover the internal discharge acoustic signal by eliminating the noises of many natures.